Longitudinal Assessment of FT3 to FT4 Conversion Ratio in Predicting the Efficacy of First-Line Pembrolizumab-Based Therapy in Advanced Non-Small Cell Lung Cancer: A Propensity-Score Matching Analysis of Data from the National Drug Monitoring Agency - Fabrizio Nelli; Enzo Maria Ruggeri; Marta Schirripa; Antonella Virtuoso; Diana Giannarelli; Armando Raso; Daniele Remotti; Agnese Fabbri (Current Oncology)
Baseline thyroid function, as measured by the fT3 to fT4 ratio, has been shown to influence the prognosis of advanced cancer patients receiving active treatments. Although immune checkpoint blockade can alter the balance of thyroid hormones, this interaction has not been thoroughly investigated. The present research sought to determine whether changes in the fT3/fT4 ratio could affect the survival outcomes of patients with advanced non-small cell lung cancer (NSCLC) who were undergoing pembrolizumab-based therapies. This study included patients with metastatic NSCLC who received pembrolizumab as upfront treatment, either alone or in combination with platinum-based chemotherapy. Relevant data were gathered before the start (time point 1) and after 12 weeks (time point 2) of treatment. From April 2018 to May 2023, we enrolled 258 eligible patients, 156 (60.5%) and 102 (39.5%) of whom were treated with single-agent or combination therapy, respectively. We stratified patients into two groups based on baseline fT3 and fT4 values [euthyroid cohort defined by fT3 and fT4 both within the normal range vs. euthyroid sick syndrome cohort defined by low fT3 and/or fT4 levels]. We examined the differences in progression-free survival (PFS) and overall survival (OS) by univariate and multivariate analyses. After applying propensity-score matching, we considered 88 relevant cases in each cohort. Longitudinal comparison of fT3/fT4 ratios showed a significant increase in the median value after pembrolizumab-based therapy (p < 0.001). We computed ROC curves to analyze the correlation between fT3/fT4 ratios and survival outcomes. The relative AUC values were not viable in predicting a positive outcome at the first time point. Conversely, assessment at the second time point revealed a significant association with PFS [AUC 0.82 (95% CI 0.75–0.89), p < 0.001] and OS [AUC 0.81 (95% CI 0.75–0.88), p < 0.001]. After a median follow-up of 20.2 (95% CI 16.2–24.2) months, the median PFS for the low and high fT3/fT4 ratio groups was 4.1 (95% CI 3.0–5.1) and 15.3 (95% CI 10.3–20.1) months, respectively (p < 0.001). The median OS for the low and high fT3/fT4 ratio groups was 6.7 (95% CI 4.9–8.5) and 19.6 (95% CI 16.4–22.8) months, respectively (p < 0.001). The multivariate analysis revealed that a low fT3/fT4 ratio was independently associated with shorter PFS [HR 2.51 (1.66–3.78); p < 0.001] and OS [HR 2.18 (1.43–3.34); p < 0.001]. After the optimal weighting of prognostic factors according to thyroid function impairment, the fT3/fT4 ratio at baseline did not affect the survival of patients receiving immune checkpoint blockade for advanced NSCLC. Patients with an increased fT3/fT4 ratio experienced a significantly decreased risk of disease progression and mortality. The longitudinal assessment of fT3/fT4 ratio may play a predictive role in this specific therapeutic setting.